Do dysfunctional coping modes mediate the relationship between perceived parenting style and disordered eating behaviours?. Issue 1 (December 2016) - Brown, Jessica; Selth, Stephanie; Stretton, Alexander; Simpson, Susan
Abstract Background Preliminary studies suggest that both childhood experiences and coping behaviours may be linked to eating disorder symptoms. Methods In this study maladaptive schema coping modes were investigated as mediators in the relationship between perceived negative parenting and disordered eating. A total of 174 adults with eating and/or body image concerns completed questionnaires measuring parenting experiences, schema modes, and disordered eating behaviours. Results Perfectionistic Overcontroller, Self-Aggrandiser, Compliant Surrenderer, Detached Protector and Detached Self-Soother coping modes partially explained the variance in the relationships between perceived negative parenting experiences and the behaviours of restricting and compensation (purging and overexercising). Conclusions Our findings suggest that Overcompensatory, Avoidant and Surrender coping mechanisms all appear to play a role in the maintenance of eating disorder symptoms, and that there are multiple complex relationships between these and Early Maladaptive Schemas that warrant further investigation.